Left atrial intramural haematoma: a fatal complication of cardiac amyloidosis—a case report. Issue 3 (2nd March 2023) - Terashima, Rika; Nakagawa, Takashi; Hara, Hisao; Hiroi, Yukio
Abstract: Background: Spontaneous left atrial intramural hematoma (LAIH) is extremely rare and there are only two cases of spontaneous LAIH involving cardiac amyloidosis (CA) reported in literature. In both cases, LAIH rapidly compromised hemodynamic stability proving to be a rare yet fatal complication. Case summary: An 83-year-old man presented with cardiogenic shock. Electrocardiogram showed complete atrioventricular block, and echocardiogram revealed severe hypokinesis and left ventricular hypertrophy. Coronary angiography revealed no significant coronary stenosis and tissue biopsy was taken from the left ventricle. The patient was intubated, placed on extracorporeal membrane oxygenation with intra-aortic balloon pump and temporary pacemaker, and admitted to ICU. Day 6 of admission, he became hemodynamically unstable, and presented with atrial fibrillation. Transesophageal echocardiography showed a newly formed large mass in the left atrium. Day 11 of admission, the patient passed away. Autopsy revealed cardiac amyloidosis and showed the mass to be a left atrial intramural hematoma. Diffuse amyloid deposits were found in the myocardium as well as the blood vessel walls of the region surrounding the LAIH. Conclusion: LAIH is a rare yet fatal complication of CA. Autopsy revealed diffuse amyloid deposits within the left atrium may lead to left atrial fragility and contribute to development of LAIH. LAIH should be considered as an important differential diagnosis in the setting of a rapidly growing left atrial mass, and in hemodynamic instability in patients with CA.